Átmeneti Románia : a román rendszerváltás történelmi, kulturális háttere - Bretter, Zoltán (Közép-Európai Közlemények, 2012)
This article aims at analyzing some aspects of the political culture in Romania at the moment of regime change. For this it makes a short historical incursion into what constituted the main characteristic of the Romanian communism, i.e. its thorough, consequent Stalinism. Beginning from 1956, under the clear impact of the Hungarian Revolution, the Romanian leadership has constantly turned to Stalin’s receipt to maintain its power. Paradoxically the Romanian society, in its large majority, has accepted the communist offer, as it incorporated basic elements of its expectations: economic self-determination, nationalistic culture, independent industry. The Romanian communist party succeeded in integrating the society and the Romanian society reinforced its historically well rooted political culture of survival. This could be the explanation why Romanian society didn’t share the same republican patterns of opposition to be seen in other East-Central European societies. A new term has been invented: „opposition trough culture”. In a somewhat distortional way this is interpreted as meaning exactly the “culture of survival”, implying acceptance rather than opposition.